ANALISIS NETRALITAS BIROKRASI PEMERINTAHAN DAERAH KABUPATEN GIANYAR (STUDI KASUS PEMBERHENTIAN SEKRETARIS DAERAH KABUPATEN GIANYAR TAHUN 2016) - Adi Pranata, Kadek Wisnu; Yudharta, Putu Dhramanu; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2019)
ABSTRACT Neutrality in the bureaucracy can be influenced by a patron-client culture, political elite intervention, and job motivation. This research was conducted on the Regional Government of Gianyar Regency. This study uses a case study with a qualitative descriptive research type. The unit of analysis in this study is head and staff in Gianyar Regency Goverment. The purpose of this study was to find out how the process of dismissal of the Regional Secretary of the Gianyar Regency was in the perspective of bureaucratic neutrality to improve the quality of the Gianyar Regency area. The technique of data collection is done by field studies, namely through observation, interviews and documentation studies. The results of the analysis show that the rational bureaucracy has not been carried out maximally and there is still political intervention in the regional government bureaucracy. Keywords: Regional Government, Rational Bureaucracy, Bureaucratic Neutrality, Regional Official